Public-private partnerships for providing behavioral health care to veterans and their families : what do we know, what do we need to learn, and what do we need to do? - Pedersen, Eric R.; Pedersen, Eric R.; Eberhart, Nicole K., 1978-; Williams, Kayla M.; Tanielian, Terri L.; Epley, Caroline; Scharf, Deborah M. (RAND Corporation, 2015)
American veterans and their family members struggle with behavioral health problems, yet few engage in treatment to address these problems. Barriers to care include trouble accessing treatment and limited communication between civilian and military health care systems, which treat veterans and their family members separately. Even though the Department of Veterans Affairs (VA) is making efforts to address barriers to care, more work is needed to effectively serve veterans and their families. Public-private partnerships have been discussed as a potential solution and could include collaborations between a public agency, such as the VA, and a private organization, such as a veteran service organization, private industry, or private hospital. Despite the call for such partnerships, not much is known about what a public-private partnership would entail for addressing behavioral health concerns for veterans and their families. The health care literature is sparse in this area, and published examples and recommendations are limited. Thus, the authors wrote this report to inform the creation of public-private partnerships to better serve veterans and their families. The report outlines nine key components for public-private partnerships addressing veteran behavioral health care. These components are supported by qualitative interview data from five successful public-private partnerships that serve veterans and their families. This report will assist policymakers in the VA and other federal agencies in developing and fostering public-private partnerships to address the behavioral health care needs of veterans and their families. The report also discusses next steps for research and policymaking efforts with regard to these partnerships.